Reconstructing the pyramid as a therapeutic approach to rheumatoid arthritis - G. Ferraccioli (PAGEPress Publications, 2011)
Several recent clinical studies have clearly established that rheumatoid arthritis (RA) is a disease identifiable since its early phases, a disease that can be adequately and efficaciously treated provided the therapeutic program can be started early on. To reach the aim of controlling effectively the disease and of leading the patients to live a normal life, several points must be fulfilled. The first is an early diagnosis obtained through a careful clinical examination along with an appropriate laboratory immunological work-up, followed by an adequate monotherapy within the first 4 months from symptoms onset. The second is the therapeutic re-assessment that needs to be done every three months, to start a possible combination therapy (COMBO), in order to rescue monotherapy failures. The third is the initiation of biological response modifiers (BRMs) within 6 months from monotherapy onset, within 3 months from COMBO in the most resistant cases. Having at hand several molecules with BRMs characteristics, we believe that the future appears much more favourable in most cases even in those with the severe disease.